4(c-3)+4=2+c-10

Simple and best practice solution for 4(c-3)+4=2+c-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(c-3)+4=2+c-10 equation:


Simplifying
4(c + -3) + 4 = 2 + c + -10

Reorder the terms:
4(-3 + c) + 4 = 2 + c + -10
(-3 * 4 + c * 4) + 4 = 2 + c + -10
(-12 + 4c) + 4 = 2 + c + -10

Reorder the terms:
-12 + 4 + 4c = 2 + c + -10

Combine like terms: -12 + 4 = -8
-8 + 4c = 2 + c + -10

Reorder the terms:
-8 + 4c = 2 + -10 + c

Combine like terms: 2 + -10 = -8
-8 + 4c = -8 + c

Add '8' to each side of the equation.
-8 + 8 + 4c = -8 + 8 + c

Combine like terms: -8 + 8 = 0
0 + 4c = -8 + 8 + c
4c = -8 + 8 + c

Combine like terms: -8 + 8 = 0
4c = 0 + c
4c = c

Solving
4c = c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
4c + -1c = c + -1c

Combine like terms: 4c + -1c = 3c
3c = c + -1c

Combine like terms: c + -1c = 0
3c = 0

Divide each side by '3'.
c = 0

Simplifying
c = 0

See similar equations:

| W^2+2w-240=0 | | 0.005(1-k)+0.03(k-7)=1 | | 7x-2=3x-14 | | 15x-9=18x-2 | | 2y=3/2x-12 | | (2x+y^2)(2y+4x-3y^2)= | | 3xy*dx+(x^2+y^2)*dy=0 | | 1/5x-1/6(x-3)=6x | | 186=(5y)(4y+3) | | -5(6-x)+6=4-7(x-2) | | ay^2+7y-8ay=56 | | 7/4=5/b | | xy*dx-(2x+4y)*dy=0 | | 2*2+y=-5 | | 2*1+y=-5 | | -3x=17+3y-z | | 2*0+y=-5 | | (4x-9)(64x^2-9)=0 | | y^2*dy=x(xdy-ydx)e^x/y | | m^3+2m^2-63m=0 | | 2(2x^2+y^2)*dx-xy*dy=0 | | [x^2+7x-71]=27 | | (2y-5)(3y+7)=0 | | 144=x+38 | | 3x-5(x-3)=-7+2x-10 | | 4*2+y=8 | | p-3u=3k | | 4*1+y=8 | | -3k=3u+-p | | 2(b-24)=44-4(b-4) | | x(x-3)(x+8)=0 | | 4*2-y=0 |

Equations solver categories